The Dynamic response of AL 2024-T3 aluminium plates impacted by projectile using small and medium scale of cluster parallel computing - Adip Kamel Abdul Ghani; Mohd Norihan Ibrahim @ Tamrin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Deformation processes of structures under ballistic impact have been investigated both experimentally and by simulation for many years now. The high complexity of impact problem is caused by the large number of factors like relative velocity of projectile and target, relative stiffness and masses, shape of colliding object, surface of contact, material characteristics and geometry and boundary conditions. Materials under ballistic impacts show highly nonlinear and dynamic behaviour including strain and strain rate hardening, thermal softening and fracture. Most of the analysis and investigation related to ballistic impact carried out by comparing the experimental results and numerical simulation. The numerical simulation period can be reduced greatly if parallel computing is applied in the simulation. The simulation procedure is carried out by using ABAQUS